REPUBLICANISM IN MODERN POLITICAL THEORY - Гайко, О. С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The article discusses the main theoretical provisions of the republican tradition in modern political theory. The main attention is focused on the works of F. Pettit and Q. Skinner. The position of the republican tradition in the political theory of the second half of the twentieth century is presented and the popularity of this tradition is argued today, the theoretical background of the actualization of republican theory is highlighted. It is shown how the republican theory was updated by the Cambridge School of the History of Political Thought. The features of the republican theory, which consists of two points, are considered: the openness of the republican project to alternative political theories (projects), representatives of the republican theory focus not on political theory, but on the history of political thought, that is, they do not develop their own theoretical project, but actualize in political theory and adapt the republican tradition to modern political practices. The origins of the republican tradition in the history of Western political thought are traced, special attention is focused on the development of republican ideas during the civil war in England (1642-1651) and the political/ideological confrontation between parliamentarians and royalists, focuses on the concepts of «political body» and «king-in-parliament». The criticism of the republican understanding of liberty by T. Hobbes and the consequences of this criticism for the political theory of the Modern era is traced. It is shown how the republican understanding of freedom is supplanted by the negative concept of freedom in modern times, why the liberal theory begins to be based on the negative concept of freedom. The republican understanding of freedom as non-domonation and the relationship between the concepts of positive liberty, negative liberty and liberty as non-domination are considered. Criticism of the republican tradition of a liberal interpretation of liberty is presented. The significance of the theoretical developments of the republican tradition for modern political theory is highlighted and the fundamental difference between the republican approach and the liberal one is shown.